Definition of the CIE standard skies and application of high dynamic range imaging technique to characterize the spatial distribution of daylight in Chile - Piderit, Maria Beatriz; Cauwerts, Coralie; Diaz, Muriel (Revista de la Construcción. Journal of Construction, 2014)
The effectiveness and accuracy of a daylighting study relies on knowing the climate and light conditions available at a given place, to then evaluate the illuminance obtained during the project development process. This paper presents the methodologies of a research process, whose objective is providing realistic data to establish the foundations for future lighting studies in Chile. It starts with the revision of the metrics used to quantify daylight; later, the methodology used to collate the monthly frequencies on four types of standard CIE skies, starting from climate files, is presented. Finally, both the methodology and the results obtained are presented to measure and characterize the real skies, as well as the High Dynamic Range photographs (HDR) and, as complement of this information, the illuminances measurements of the sky dome to define the types of skies of six Chilean cities. From the study applied, it is possible to conclude that knowing the standard CIE skies of a place allows us to adjust and focus the daylighting study for predetermined and predominant skies. It is just as important to mention that the measuring techniques for the skies must be adjusted and calibrated for each studied location.